Insight Into the Prospects for the Improvement of Seed Starch in Legume—A Review - Tayade, Rupesh; Kulkarni, Krishnanand P.; Jo, Hyun; Song, Jong Tae; Lee, Jeong-Dong (Frontiers in Plant Science, 2019)
In addition to proteins and/or oils, mature seeds of most legume crops contain important carbohydrate components, including starches and sugars. Starch is also an essential nutritional component of human and animal diets, and has various food and non-food industrial applications. Starch is a primary insoluble polymeric carbohydrate produced by higher plants, and consists of amylopectin, and amylose as a major fraction. Legume seeds are not only an affordable source of protein, but also the starch, which has an advantage of being resistant starch compared to cereal, root and tuber starch. For these reasons, legume seeds form a good source of resistant starch-rich healthy food with a high protein content, and can be utilized in various food applications. The genetics and molecular details of starch and other carbohydrate contents are well-studied in cereal crops, but have received little attention in legumes. In order to improve legume starch content, quality and quantity, it is necessary to understand the genetic and molecular factors regulating carbohydrate metabolism in legume crops. In this review, we assessed the current literature reporting the genetic and molecular basis of legume carbohydrate components, primarily focused on seed starch contents. We provided an overview of starch biosynthesis in the heterotrophic organs, the chemical composition of major consumable legumes, the factors influencing starch digestibility, and advances in the genetic, transcriptomic, and metabolomic studies in important legume crops. Further, we discussed breeding and biotechnological approaches for the improvement of the starch composition in major legume crops. The information reviewed in this study will be helpful in facilitating the food and non-food applications of legume starch and provide economic benefits to farmers and industries.